The Phenomenon of Natural Resources Exploitation in ‘Mencari Ujung Pelangi': An Ecocritic Approach - Wardani, Yohana Ari (Universitas Airlangga, 2024)
Environmental crisis has become a current issue for literary researches globally including in Indonesia. 'Mencari Ujung Pelangi' through an ecocritical approach, is providing a nuanced backdrop against which to explore the intricate dynamics of natural resource exploitation within literary contexts. This study is using eco-crititicism lens since it focuses on the relationship between literature and the environment. For the purpose of this study, the questions formulated were 1) How does